PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS PERUSAHAAN, SOLVABILITAS PERUSAHAAN DAN LIKUIDITAS PERUSAHAAN TERHADAP PENUNDAAN AUDIT PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rattu, Nikita Melisa; Saerang, David Paul Elia; Nangoi, Grace (Universitas Sam Ratulangi, 2015)
Presentation of information can be useful when presented accurately and timely when needed by users of financial statements.Audit report is financial statetements audited by the auditor. The information contained in the financial statements referred helpful if presented accurately and timely, which is available when needed by the users of financial statements, such as creditors, investors, governments, communities and other parties as a basis for making a decision . The data used are secondary data, the financial statements of nine companies from food and beverage sub-sectors listed in Indonesia Stock Exchange in 2010-2013. To prove the hypothesis,used multiple regression testing partial test concluded that the profitability, solvency, Company Size and Liquidity not significantly affect audit delay in the sub-sector firms in the food and beverage IDX. Simultaneous testing concluded that the profitability, solvency, Company Size and Liquidity simultaneously no significant effect on the Audit Delay companies sector food and beverage sub IDX